2021
DOI: 10.1177/14777509211036643
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow donation in Poland: 2021 update, and the impact of the coronavirus disease 2019 pandemic on haematopoietic stem cell transplantation

Abstract: Haematopoietic stem cell transplantation is a treatment modality that saves the health and lives of a growing number of patients around the world. In the majority of cases, the procedure is conducted to treat haematologic neoplasms, although it can also be used as a therapy for some non-haematooncological diseases. The progress that has been taking place in the field of haematopoietic stem cell transplantation involves the need for recruiting more and more potential unrelated bone marrow donors for allotranspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Recruitment of donors also significantly declined because the DKMS stopped public offline donor recruitment, resulting in a 40% wane in new donors during the pandemic 39 . Similar struggles with bone marrow donor recruitment were also seen in other countries like Poland 40 .…”
Section: Section 1: Changes To Transplant and Cellular Therapy Delive...supporting
confidence: 66%
“…Recruitment of donors also significantly declined because the DKMS stopped public offline donor recruitment, resulting in a 40% wane in new donors during the pandemic 39 . Similar struggles with bone marrow donor recruitment were also seen in other countries like Poland 40 .…”
Section: Section 1: Changes To Transplant and Cellular Therapy Delive...supporting
confidence: 66%
“…Thus, similar programs are warranted at the national level and could be integrated into the curriculum or extracurricular activities of medical schools in Saudi Arabia. To increase awareness at the public level, a recent Polish experience was reported by Janowiak-Majeranowska et al [25], in which they found that exploiting social media and organizing national days that were designed to improve public knowledge about HSCT seemed promising. These ideas seem doable and can also be applied to our community in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the application of a bone marrow (BM) transplant in hematological diseases, especially hematological malignancies, primary immunodeficiency, and some solid tumors, have become the treatment of choice [3][4][5][6][7][8]. The multiplicity of cases involving cancerous diseases of this type, and the increasingly younger age of patients, forces modern societies to accept the necessity for developing the idea of donation and recruitment of a suitable number of potential donors [1,[9][10][11], and hence contributing to saving many patients. Among donations, one important type is the altruistic donation of a living person, with particular consideration of donation designed to benefit unrelated people (Living Anonymous Donation to a Stranger-LADS).…”
Section: Introductionmentioning
confidence: 99%